2022
DOI: 10.1093/ofid/ofac089
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Humoral and Cellular Immune Responses of Patients With HIV After Vaccination With BNT162b2 mRNA COVID-19 Vaccine in the Tel-Aviv Medical Center

Abstract: Background Little is known about vaccine efficacy and sustainability among people with HIV (PWH). We estimated humoral and cellular immune responses post-vaccination with BNT162b2 mRNA COVID-19 vaccine among PWH in Tel-Aviv medical center. Methods The vaccine humoral response was evaluated by measuring IgG titers of anti-spike receptor-binding domain antibodies (anti-RBD IgG). Cellular response was assessed by stimulating don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Our study has important limitations. Our single academic center cohort comprised PWH ≥ 55 years with well-controlled HIV, robust CD4 counts, which may not represent HIV-infected cohorts with dissimilarities and a younger cohort of people living with HIV [ 12 ]. However, it does provide important insight about older PWH, a demographic increasing annually as majority of US PWH are ≥ 50 years [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has important limitations. Our single academic center cohort comprised PWH ≥ 55 years with well-controlled HIV, robust CD4 counts, which may not represent HIV-infected cohorts with dissimilarities and a younger cohort of people living with HIV [ 12 ]. However, it does provide important insight about older PWH, a demographic increasing annually as majority of US PWH are ≥ 50 years [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLWH who received the Novavax vaccine had attenuated humoral immune responses [ 66 ] as did those who received CoronaVac [ 67 ]. A cohort 136 PLWH who received mRNA vaccination demonstrated comparable humoral and cellular responses, although those with CD4 + T-cell counts < 300 cells/µL had lower binding antibodies [ 68 ]. The question of whether additional booster vaccination attenuates potential differences in immune responses among PLWH with lower CD4 + counts and unsuppressed viral loads merits further study.…”
Section: Protection From Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…A critical point in the persistence of vaccinal immunity overtime is the induction of cellular immune memory. Recent works have demonstrated the presence of spike-specific T cells in PLWHIV vaccinated with two doses of mRNA vaccine, no different compared to HCs (9,24). Here, we demonstrated that spike-specific B cells were at a comparable rate in PLWHIV and HCs.…”
Section: Discussionmentioning
confidence: 98%